The development of a novel multiepitope vaccine targeting the secretion systems of Pseudomonas aeruginosa using a reverse vaccinology and immunoinformatic strategy - Tohid Piri-Gharaghie; Marjaneh Ebrahimi; Behnaz Dehganzad; Zahra Seraj (Discover Applied Sciences)
Abstract The emergence of multidrug-resistant Pseudomonas aeruginosa strains poses a significant public health risk due to the high morbidity and mortality associated with invasive infections. Despite extensive efforts, vaccine candidates targeting P. aeruginosa have failed in clinical trials, and there is currently no authorized vaccination available. This study using reverse vaccinology identified potential immunization candidates against P. aeruginosa. The study collected potential immunogenic targets and evaluated them using analyses. The antigens were organized into nine different vaccine constructs, and the immunity index for the top three vaccines was 1.52, 1.53, and 1.53, respectively. An enhanced formulation using these potentially immunogenic proteins and careful adjuvant selection could facilitate complete immunization.